The applicability of New Public Management (NPM) in the Yemeni public sector - Basaloom, Rami Salmeen Mohammed (Kulliyyah of Economics and Management Sciences, International islamic University Malaysia, 2017)
New Public Management (NPM) is a new innovation in the public sector of Yemen. It is presently fashionable and presented as the best way to govern organisations and improve accountability in the public sector. The emphasis on Yemen is important because research on the NPM is limited in developing countries. The specific factors influencing this research in Yemen are derived from the crisis of governance. This study extends the literature by investigating the possibility of applying NPM in crisis states, especially in Yemen. As a result, this study conducted an exploratory research to study NPM reform. It investigated the prospect of applying the NPM in Yemen and identified the critical factors for successful application of the NPM to improve the efficiency of the Yemeni public sector. Data was collected from a survey of 200 government employees and officers (executive manager, general manager deputy manager, operational manager, and head of the department) working in the 14 ministries at the central government of Yemen in Sana'a “Amanat Al-Asemah”. The result shows that the use of information technology, the quality of human resource, and budget management orientation highly contribute to the adoption of the NPM innovation in Yemen's public sector. Moreover, private sector management style is considered key for the implementation ofthe NPM in Yemen. Otherwise, the downsizing elements were ranked the least significant for NPM implementation.